LINGUISTIC FEATURE OF ENGLISH RIDDLES (Scientific journal of the Fergana State University, 2025)
The importance of riddles in oral literature and folklore is examined in this essay. Riddles are questions and tasks that are usually written in a poetry or prose form. They concentrate on contrasting one item or occurrence with another to find a characteristic, form, behavior, state, or function that is deliberately hidden.